Impacts of herbal medicines on hot flash: a systematic review - Z Yousefi; N Abdollahpour; M Ghazanfarpour; R Sadeghi; N Pourmoghadam (Institue of Medicinal Plants, ACECR, 2016)
Background: the most common symptoms experienced by women are Hot flashes are around the time of menopause. Many women are interested in herbal medicines because of fear of side effect of Hormone therapy. Objective: In this study, we seek to assess the effectiveness of herbal medicine on the recurrence of hot flash in menopausal women. Methods: The database of MEDLINE, Scopus, and the Cochrane Central Register of Controlled Trials (RCT) were searched to investigate trials on the efficacy of herbal medicines on hot flash. Results: RCTs were incorporated into this accurate review, with the results demonstrating that herbal medicines such as evening primrose, oil hop and Valerian, red clover, of black Cohosh flaxseed and hypericum perforatum can ease the side effects of hot flash. Conclusion: Our study indicated that herbal medicines can reduce the negative effects of hot flash. However, desirable impacts still remain indeterminate due to the number of RCTs, limited sample size and unsystematic methodology. As such, larger RCTs with more reliable design and improved measurable reporting of the outcomes are required to support this conclusion.